Turystyka jako determinanta rozwoju obszarów wiejskich: Tourism as a determinant of rural development - Marciniuk-Kluska, Anna (Management and Administration Journal, 2021)
The paper elaborates on the issues showing the need for the development of tourism at the level of local government units, i.e. communes and districts. Special attention is paid to the benefits deriving from the development of tourism and the possibility of creating conditions facilitating tourism development by communes. A very important element in the tourism development at the level of a commune or district is the positive attitude of local authorities, bodies which can strongly and diversely support the development of tourism. This can be done by adequate promotion, especially by communes and tourism organisations. Local area natural values or protected landscape areas are only two of many factors significant in the development of tourism in a given commune.